Development of a new tuned vibration absorber based on one degree-of-freedom of translational motion. Issue 1 (1st January 2021) - Almashhor, Abobakr; Asiri, Saeed A.
Abstract: The study has proposed a newly tuned vibration absorber (TVA) based on one degree-of-freedom (1DOF) of translational motion. The absorber mass takes the shape of a tank filled with fluid. The device has been attached to the fluid circulating system, which plays the role of changing the absorber mass. It fills the tank or drains it depending on the data received from the frequency force sensor. The type of TVA used is similar to simple damped TVA. A MATLAB software has been applied, and a numerical procedure was used to test the TVA and compare the performance with the other TVAs. The method is simple to carry out the performance of the TVA as it is adequate for real-life problems.